Sex‐differential associations between cognitive impairments and white matter abnormalities in first episode and drug‐naïve schizophrenia. Issue 5 (15th October 2020) - Yang, Mi; Gao, Shan; Xiong, Weisen; Zhang, Xiang Yang
Abstract: Aim: Previous evidence has suggested that schizophrenia patients may display sex differences in cognitive impairments and cognitive impairments are related to disrupted white matter (WM) microstructure. The current research aims to address the intriguing possibility for the sex‐specific association between cognitive deficits and WM abnormalities in first‐episode and drug‐naïve schizophrenia. Methods: Cognitive performance on the Measurement and Treatment Research to Improve Cognition in Schizophrenia (MATRICS) Consensus Cognitive Battery (MCCB) was measured in 39 FEND patients (females:males = 23:16) and 30 healthy controls (females:males = 17:13), together with whole‐brain WM fractional anisotropy (FA) values determined using voxel‐based diffusion tensor imaging. Correlations between cognitive performance and FA values were assessed. Results: Patients performed significantly worse than healthy controls in the total score and most of the subscores of MCCB. Female patients displayed better cognitive performance than male patients on the Trail Making A Test, the Hopkins Verbal Learning Test and the Spatial Span Test in the Wechsler Memory Scale. More importantly, sex‐differential association between cognitive performance and FA values was found in patients, but not in healthy controls. In particular, FA values in the cerebellum were negatively correlated with the continuous performance and digital sequence scores in male patients but positively correlated with the performance on the Spatial Span Test in the Wechsler Memory Scale in female patients. Conclusions: These findings suggest sex‐specific neurobiological substrates involved in cognitive deficits in early‐onset schizophrenia and have important implications for differentially targeted interventions between males and females.